2006
DOI: 10.1063/1.2227560
|View full text |Cite
|
Sign up to set email alerts
|

Potential of discharge-based lithium plasma as an extreme ultraviolet source

Abstract: Articles you may be interested inA point-like source of extreme ultraviolet radiation based on a discharge in a non-uniform gas flow, sustained by powerful gyrotron radiation of terahertz frequency band High conversion efficiency mass-limited Sn-based laser plasma source for extreme ultraviolet lithography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It can play a crucial role in the development of extreme ultraviolet lithography source, thin film deposition, synthesis of nanoparticles, metallic atomic beam source for accelerators, and probing neutral atomic beam in plasma environment (Chrisey & Hubler, 1994;Geohegan et al, 1998;Doria et al, 2004;Fazio et al, 2009;Hoffman, 2009;Huber et al, 2005;Masnavi et al, 2006;Nardi et al, 2009;Sizyuk et al, 2007;Wolowski et al, 2007;Wang et al, 2007). Several attempts have been made to optimize the expanding laser produced plasma plume by varying experimental factors like, ambient gas, focal spot size, laser pulse width, irradiance, and wavelength of ablating laser (Key et al, 1983;Bulgakova et al, 2000;Amoruso et al, 2003;Harilal, 2007;Beilis, 2007;Laska et al, 2008;Rafique et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…It can play a crucial role in the development of extreme ultraviolet lithography source, thin film deposition, synthesis of nanoparticles, metallic atomic beam source for accelerators, and probing neutral atomic beam in plasma environment (Chrisey & Hubler, 1994;Geohegan et al, 1998;Doria et al, 2004;Fazio et al, 2009;Hoffman, 2009;Huber et al, 2005;Masnavi et al, 2006;Nardi et al, 2009;Sizyuk et al, 2007;Wolowski et al, 2007;Wang et al, 2007). Several attempts have been made to optimize the expanding laser produced plasma plume by varying experimental factors like, ambient gas, focal spot size, laser pulse width, irradiance, and wavelength of ablating laser (Key et al, 1983;Bulgakova et al, 2000;Amoruso et al, 2003;Harilal, 2007;Beilis, 2007;Laska et al, 2008;Rafique et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, we adopted lithium as the plasma source which has a narrow and strong spectrum at 13.5 nm wavelength [2]. By using the counter-facing plasma focus system and lithium source, we aim to improve the energy conversion efficiency, spectral efficiency and repetition capability [3,4]. Figure 1 shows the operating principle of the counter-facing plasma guns.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Comprehensive analysis has been performed for the ionization physics and radiation transfer. 6 However, the conventional approaches have been shown to be unable to give a source with required characteristics: a high average power with a small size of the source for projection lithography. 7,8 It has also been shown that at a fixed input power the EUV emission produced by multiply charged ions has a maximum, P max , at an optimal electron density N e,opt and electron temperature T e,opt : 6 ion recombination or ionization accompanying, for example, a temperature decrease or increase changes the ionization balance with a reduction in line emission.…”
Section: Introductionmentioning
confidence: 99%
“…These negative processes cannot be easily suppressed because the power of plasma radiation for the conditions is too low to control the total plasma energy balance; the use of the blackbody radiation, ϳT e 4 , may considerably reduce the efficiency of line radiation due to absorption. 6,9 Practically so far in the DPP studies, the dynamic compression of fuel gas by z-pinch and vacuum spark discharges with a drive current of few tens of kiloamperes is mainly used for producing the plasma column with the required EUV parameters. In z-pinches, a high temperature and a high density are achieved during the stagnation in its implosion phase.…”
Section: Introductionmentioning
confidence: 99%